ANALYSE SEMIO-PRAGMATIQUE DE LA DECLARATION POLITIQUE DU PRESIDENT FELIX TSHISEKEDI LORS DE SA TOURNEE A LODJA, PROVINCE DU SANKURU. : APPROCHE CRITIQUE DE LA COMMUNICATION DUN LEADER POLITIQUE - Batsu, Henri Paul IYELE (IJRDO - Journal of Social Science and Humanities Research, 2022)
The observation done on the declaration of President Felix Antoine Tshisekedi Tshilombo during his tour un Lodja, in the Province of Sankuru is ideologically too marked and criticized in Congolese political spce African countries and westerns. For some, the ideological range of this political declaration of the Congolese president reveals ambiguity which characterizes his ideology to already conduct a pre-electoral campaign while it remains fir him 22 months to whistle the end of his quinquennium. The analyses done in the piece of the extract of political speech or declaration of the Congolese president in Lodja the 5th January 2022 has fed national et international public opinion in the eyes from which is born ambiguities in the interpretation helping up the political thinking of the locator with numerous ideological places, the positive connotations, and above all negatives, general truth as well as the citations the propositions of action. So, the emergency to found a solution to Congolese problems. For others, which cannot be the ideologies corresponding to his obedience, the speaker has just told the truth face to present really the state of destruction of basic infrastructures; a state of things that the denies neither to be the author nor reveals his responsibility. His declaration is, for them, a constative speech rather than commissive. As the act of constative speech, the speaker of Lodja, for restoring the balanced broken social and politics to telle the truth for being sincere, just and rational. Face to this discursive ambiguity, his speech has been on the values that recommends the democratic guest with is a solution to the crisis submissive to the control of Christian and respublican values for the development of his country during his mandate. The ambiguity is found at diverse levels of reality: on the equivocal plan (double sense), on the logical plan (contradiction), on discursive plan (implicitation of real established regarding to the daily life of his population) and on the plan of behavior (discrepancy between accomplishment).